2012
DOI: 10.1159/000339028
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Cardiac Effects of DPP-4 Inhibitors – from Preclinical Development to Clinical Research

Abstract: Inhibitors of type 4 dipeptidyl peptidase (DDP-4) were developed and approved for the oral treatment of type 2 diabetes. Its mode of action is to inhibit the degradation of incretins, such as type 1 glucagon like peptide (GLP-1), and GIP. GLP-1 stimulates glucose-dependent insulin secretion from pancreatic beta-cells and suppresses glucagon release from alpha-cells, thereby improving glucose control. Besides its action on the pancreas type 1 glucagon like peptide has direct effects on the heart, vessels and ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
114
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(121 citation statements)
references
References 99 publications
(131 reference statements)
5
114
0
2
Order By: Relevance
“…8 Recently, investigations of DPPIV have focused on identifying new physiologically relevant substrates, such as RANTES, neuropeptide Y, and substance P. 9,10 High-mobility group box-1 (HMGB-1) protein is a cytokine identified in 2012 as a substrate of DPPIV that mediates responses to infection, injury, and inflammation. 11,12 A 2012 paper proposed HMGB-1 as a causative factor in renal damage.…”
mentioning
confidence: 99%
“…8 Recently, investigations of DPPIV have focused on identifying new physiologically relevant substrates, such as RANTES, neuropeptide Y, and substance P. 9,10 High-mobility group box-1 (HMGB-1) protein is a cytokine identified in 2012 as a substrate of DPPIV that mediates responses to infection, injury, and inflammation. 11,12 A 2012 paper proposed HMGB-1 as a causative factor in renal damage.…”
mentioning
confidence: 99%
“…These results demonstrated, for the first time, that switching to a small dose of sitagliptin based on the renal function has been demonstrated to be effective and safe when administered to the T2DM patients with moderate to severe renal dysfunction. The renal excretion rates as unchanged sitagliptin, alogliptin, vildagliptin, and linagliptin were reported to be 80, 60-71, 21, and < 6%, respectively, showing a higher excretion rate of sitagliptin in the urine compared to any other DPP-4 inhibitors [20]. The concentration of sitagliptin at a decreased dose depending on the degree of renal dysfunction in the tubular lumen was unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that DPP-4 inhibitors have antiinflammatory effects and can improve bone marrow function [45,46]. The possibility of scission protection by DPP-4 with antiinflammatory agents such as BNP/ANP (brain natriuretic peptide/atrial natriuretic peptide) or NPY (neuropeptide), which are substrates of DPP-4, is suggested, and an intracorporeal inflammation condition is therefore thought to be ameliorated by DPP-4 inhibitor [47][48][49][50]. This may explain the improved iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%